#CCV- > KV-: CORPUS-BASED EVIDENCE OF HISTORICAL CHANGE IN ENGLISH PHONOTACTICS - Schreier, Daniel (International Journal of English Studies, 2009)
This paper examines modifications in the phonotactic system of English, as attested in changes that affected the tactic behaviour of individual consonants. This is exemplified by the loss of initial clusters in English (#CC- > #C-), which resulted in a merger of the cluster with a single consonant and effectively changed the syllable structure to CV-; this affected initial clusters such as */kn-1, */wl-1 or */hr-/. A corpus-based study traces these changes and dates them to various periods of the historical evolution of English. The findings suggest that multiple causations can be put forward to explain phonotactic change in English, including continuation of changes inherited from Germanic (and completed in Middle English), putative contact influence with Norman French, as well as local, independent innovation. Moreover, the trajectory of loss is traced also, which indicates that phonotactic change proceeds in similar fashion to other linguistic innovations (namely in an S-curve trajectory).